2020
DOI: 10.1002/cche.10379
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different levels of heat‐treated legume flour on nutritional, physical, textural, and sensory properties of gluten‐free muffins

Abstract: Background and objectives There is an increasing interest in the development of gluten‐free products for patients with celiac disease and nonceliac consumers. Three different ratios (80:20, 65:35, and 50:50) of legume flour to waxy rice flour and two legume species (mungbean and cowpea) were used to prepare gluten‐free muffins. Chemical composition, physical properties, texture, and sensory attributes of these muffins were evaluated. Findings Legume‐based muffins had lower specific volume but higher firmness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In some studies, the overall flavor acceptability scores of products decreased with increase in the level of supplementation of pulse‐ingredients as demonstrated for bread supplemented with coarse navy bean flour (Borsuk, 2011), muffins containing cowpea flour (Jeong et al., 2021), noodles formulated with pea, lentil, or faba bean hull powder (Kaya et al., 2018), crackers containing germinated lentil extract (Polat et al., 2020), and yogurt supplemented with pea or lentil flour (Zare, 2011), without the flavor notes being specified. Although the flavor notes were not specified in these studies, it is highly likely that the flavor was characteristic of pulses, for example, beany flavor.…”
Section: Influence Of Pulses and Their Derived Ingredients On Sensory...mentioning
confidence: 99%
“…In some studies, the overall flavor acceptability scores of products decreased with increase in the level of supplementation of pulse‐ingredients as demonstrated for bread supplemented with coarse navy bean flour (Borsuk, 2011), muffins containing cowpea flour (Jeong et al., 2021), noodles formulated with pea, lentil, or faba bean hull powder (Kaya et al., 2018), crackers containing germinated lentil extract (Polat et al., 2020), and yogurt supplemented with pea or lentil flour (Zare, 2011), without the flavor notes being specified. Although the flavor notes were not specified in these studies, it is highly likely that the flavor was characteristic of pulses, for example, beany flavor.…”
Section: Influence Of Pulses and Their Derived Ingredients On Sensory...mentioning
confidence: 99%
“…They are traditionally formulated using wheat flour, fat, sugar, egg, milk and baking powder, which generate the typical spongy texture, porous structure and high volume (Singh et al ., 2015; Jeong & Chung, 2019). There have been increasing interests in the development of muffins free of gluten for celiac patients and consumers interested in wheat‐free foods (Singh et al ., 2015; Jeong et al ., 2021). Gluten is essential for special baking quality as it provides unique elasticity and extensibility to dough (Jeong et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There have been increasing interests in the development of muffins free of gluten for celiac patients and consumers interested in wheat‐free foods (Singh et al ., 2015; Jeong et al ., 2021). Gluten is essential for special baking quality as it provides unique elasticity and extensibility to dough (Jeong et al ., 2021). Thus, it is difficult and challenging to replace wheat flour and produce high‐quality gluten‐free muffins.…”
Section: Introductionmentioning
confidence: 99%
“…The protein content (4.4 g/100 g) of rice-based pizza also increased (7.3-7.4 g/100 g), when supplemented with lentils (10/100 g) (Pasqualone et al, 2022). In the same vein, the protein content of muffins prepared with 80:20, 65:35, and 50:50 legume-waxy rice combinations increased (6.4-9.0%) as the proportion of legume flour (50, 65, and 80%, respectively) increased (Jeong et al, 2020). Most studies showed that adding legumes to the GFFs increased their protein content more than other nutrients, such as carbohydrates, minerals, and lipids.…”
Section: Legumes As Sources Of Protein In Gffsmentioning
confidence: 82%